Control of two-wheels inverted pendulum mobile robot using full order sliding mode control - Nawawi, S. W.; Osman, Johari H. S. (2006)

(untitled)
The research on two-wheel inverted pendulum or commonly call balancing robot has gained momentum over the last decade in a number of robotic laboratories around the world This paper deals with the modeling of 2-wheels Inverted Pendulum and the design of Full Order Sliding Mode Control (FOSMC) for the system. The mathematical model of 2-wheels inverted pendulum system that is highly nonlinear is derived. The final model is then represented in state-space form and the system suffers from mismatched condition. A robust controller based on Sliding Mode Control is proposed to perform the robust stabilization and disturbance rejection of the system. A computer simulation study is carried out to access the performance of the proposed control law.